2021
DOI: 10.1109/access.2021.3053409
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Near the Edge: Increasing the Energy Efficiency of FFTs on GPUs for Real-Time Edge Computing

Abstract: The Square Kilometre Array (SKA) is an international initiative for developing the world's largest radio telescope with a total collecting area of over a million square meters. The scale of the operation, combined with the remote location of the telescope, requires the use of energy-efficient computational algorithms. This, along with the extreme data rates that will be produced by the SKA and the requirement for a real-time observing capability, necessitates in-situ data processing in an edge style computing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Lowering the memory traffic requirement of FDAS has led to an approximately 1.6× speedup. The improved compute performance of bfloat16 is not a factor in this case, as the pipeline is memory bandwidth bound, with a low computational overhead (Adámek 2021). The speedup enables users of GPU-accelerated FDAS to increase their pulsar parameter search space on a given set of hardware when performing a real-time search, or to reduce their upfront hardware requirement for a given search.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowering the memory traffic requirement of FDAS has led to an approximately 1.6× speedup. The improved compute performance of bfloat16 is not a factor in this case, as the pipeline is memory bandwidth bound, with a low computational overhead (Adámek 2021). The speedup enables users of GPU-accelerated FDAS to increase their pulsar parameter search space on a given set of hardware when performing a real-time search, or to reduce their upfront hardware requirement for a given search.…”
Section: Discussionmentioning
confidence: 99%
“…When performing FDAS, AA spends a significant fraction of the runtime performing GPU-accelerated FFTs. The performance of a GPU-accelerated FFT is limited by memory bandwidth on current-generation hardware (Adámek 2021), and so by reducing the numerical precision of the calculations from 32 to 16 bits, this bottleneck can be alleviated simply by halving the amount of data that need to be transported to and from the GPU processing cores.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, the Fast Fourier Transform (FFT) has been used to convert the received resultant signals into the frequency domain. Specifically, the Discrete Fourier Transform (DFT) [31,33,34] is applied to improve the computational complexity. The frequency content of the input signal x is then extracted using the following transformation:…”
Section: Frequency Domain Analysismentioning
confidence: 99%
“…Edge computing is a key enabling technology that reduces latency, thus significantly enabling many real-time applications. Adámek et al [35] demonstrated the benefit of using edge computing to reduce the total power consumption of data processing. In addition, the authors demonstrated an average of 43% reduction in power consumption by optimizing the frequency scaling of core clocks on NVIDIA A100 GPU.…”
Section: Edge Computingmentioning
confidence: 99%